Development of the main directions on protection mountain and meadow peaty soils of basins of the rivers of the Northeast slope of Greater Caucasus. Issue 4 (1st October 2016) - Mardanov, Ilham Ildirim oglu
Abstract: Mountain territories of the Azerbaijani part of Greater Caucasus differ increasing impact of different types of human activity on mountain meadow landscape complexes with their unpredictable consequences to which research works of many scientists are devoted. For this reason there is a need of implementation of the complex analysis of conditions of formation of mountain meadow peaty soils, their physical and chemical indicators and structure, opportunities of implementation of urgent nature protection actions.